Convective Self‐Aggregation As a Cold Pool‐Driven Critical Phenomenon. Issue 7 (8th April 2019) - Haerter, Jan O.
Abstract: Convective self‐aggregation is when thunderstorm clouds cluster over a constant temperature surface in radiative convective equilibrium. Self‐aggregation was implicated in the Madden‐Julian Oscillation and hurricanes. Yet, numerical simulations succeed or fail at producing self‐aggregation, depending on modeling choices. Common explanations for self‐aggregation invoke radiative effects, acting to concentrate moisture in a subdomain. Interaction between cold pools, caused by rain evaporation, drives reorganization of boundary layer moisture and triggers new updrafts. We propose a simple model for aggregation by cold pool interaction, assuming a local number density ρ (r ) of precipitation cells, and that interaction scales quadratically with ρ (r ). Our model mimics global energy constraints by limiting further cell production when many cells are present. The phase diagram shows a continuous phase transition between a continuum and an aggregated state. Strong cold pool‐cold pool interaction gives a uniform convective phase, while weak interaction yields few and independent cells. Segregation results for intermediate interaction strength. Key Points: Convective self‐aggregation can result from cold pool interaction and global energy constraints alone A model is presented, which shows a phase transition between a uniform state and an aggregated state, as cold pool interaction is increased The phase diagram is mapped out in 2‐D space spanned by spontaneous generation and interaction strength, showing where aggregation dominates